BALINESE WOMEN IN DIVORCE AND ITS SETTLEMENT (FROM HISTORICAL AND GENDER PERSPECTIVES) - Mahyuni, Ida Ayu Putu; Wirawan, AA Bagus; Ariani, I Gusti Agung; Wiasti, Ni Made (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2016)
Cultural and structural injustice resulting from the difference in genre which has been strongly adhered to by the Balinese community has been responsible for divorce, its settlement, and its implication on the Balinese women in Denpasar City. This study was intended to deconstruct, anticipate and implant the concept of structural and cultural injustice resulting from the difference in genre. The data were qualitatively analyzed using the analysis of gender. The theories used were the critical theory of postmodern such as the theory of hegemony and the theory of deconstruction and the other critical theories which are relevant to the present study. The result of the study shows that the divorce undergone by the Balinese women was the manifestation of the structural and cultural injustice resulting from the difference in gender. The decisions made through the traditional law and the Act Number 1 of 1974 concerning Divorce are still biased in regard to genre. The divorce undergone by the Balinese women affected the related families (the ex-wife’s family, the ex-husband’s family, and the other families related to them. The patriarchal ideology caused the Balinese women to be marginalized and subordinated and sensitive to both physical and psychological coercions. Economically, they were also neglected. The injustice in gender could also be eternalized through legal regulations. The Act Number 1 of 1974 concerning Marriage is still biased; it still refers to the traditional law which benefits men in divorce.